(untitled) (Indian Journal of Pure & Applied Physics (IJPAP), 2026)
Split Ring Resonator (SRR) antennas provide better electromagnetic characteristics and are used in various wireless applications. The designed antenna is developed on a cost effective FR4 substrate with dimensions of 35 x 35 mm² that features a simple and effective radiating geometry over it. This paper provides an overview of SRR antennas, with a focus on their design, mechanism, and ability to use in multiple frequency bands. The novelty of the designed SRR antennas is in their ability for manipulating the electromagnetic wave in the presence of resonators for the desired applications. The SRR antenna, with a focus on the use of slots in ground planes is used for improvement in frequency and bandwidth in wireless communication systems. Partial ground planes are used in the designed antenna for further improvement of radiation characteristics. The designed antenna is fabricated and measured for the validation of results. The measured results confirm that the designed antenna shall be utilized in worldwide interoperability for microwave access (WiMAX) communication, industrial, scientific, and medical radio band (ISM) communication, and in Sub-7 GHz fifth generation (5G) wireless communication.